Legal Analysis of the Position of Heirs Who Change Religion According to Civil Law and Islamic Law - Wulandari, Ina; Kusriyah, Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study aims to analyze: 1) The position of heirs who change religions according to civil law and Islamic law. 2) Legal protection that can be guaranteed for heirs who change religions. This type of research is included in the scope of normative legal research. The approach method in this study is the statute approach. The type and source of data in this study are secondary data obtained from literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1) The position of heirs who change religions according to civil law and Islamic law, namely civil law does not differentiate heirs based on religion. There is no prohibition for heirs of different religions to inherit the testator's inheritance. While Islamic law does not provide inheritance rights by kinship to heirs who change religions. Heirs who change religions cannot inherit property from Muslim testators. However, the provision of property between people of different religions can still be done in the form of grants, wills, and gifts. If there is an heir who changes religion, the heir should discuss it with the other heirs before he dies. 2) Legal protection that can be guaranteed for heirs who change religions can be guaranteed through several mechanisms, namely the Civil Code still provides inheritance rights regardless of religion, while Islamic Law can still provide rights through grants or wills. Through a family mediation approach, a peaceful agreement can also be reached. An approach through mediation or family agreement can be a peaceful and mutually beneficial solution. With mediation, families can reach an agreement on the division of assets fairly, including providing a portion for heirs who change religions. This path allows for out-of-court settlements, avoids conflict, and maintains good relations between family members. This protection is in line with the principle of justice in Maqasid Syariah and Human Rights to ensure that the rights and welfare of heirs remain protected.